2016
DOI: 10.4137/bmi.s33372
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator System and Breast Cancer: Potential Role in Therapy Decision Making and Precision Medicine

Abstract: Shifting from the historical TNM paradigm to the determination of molecular and genetic subtypes of tumors has been a major improvement to better picture cancerous diseases. The sharper the picture is, the better will be the possibility to develop subsequent strategies, thus achieving higher efficacy and prolonged survival eventually. Recent studies suggest that urokinase-type plasminogen activator (uPA), uPA Receptor (uPAR), and plasmino-gen activator inhibitor-1 (PAI-1) may play a critical role in cancer inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…EGFR is not only implicated in the promotion of tumour growth by promoting angiogenesis and revascularization, but EGFR signalling pathways are also related to up‐regulation of PLAU and PLAUR . Plasmin is also capable of activating several MMPs, including MMP3, which may lead to extracellular matrix degradation . Our network outcome model indicated that EGFR was significantly associated with lower mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…EGFR is not only implicated in the promotion of tumour growth by promoting angiogenesis and revascularization, but EGFR signalling pathways are also related to up‐regulation of PLAU and PLAUR . Plasmin is also capable of activating several MMPs, including MMP3, which may lead to extracellular matrix degradation . Our network outcome model indicated that EGFR was significantly associated with lower mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Besides its roles in thrombosis and atherosclerosis, other roles related studies were relatively rare. However, studies indicated that PAI-1 is present in increased levels in various disease states (such as some forms of cancer), as well as in obesity and the metabolic syndrome [20-22]. In inflammatory conditions, PAI-1 appears to play a significant role in the progression to fibrosis, which is pathological formation of connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic relevance of components of the plasminogen activator system has been intensively studied in various cancers (Duffy and Duggan 2004;Ferrier et al 2000;Baluka et al 2016). In breast cancer patients, high tissue levels of uPA and PAI-1 are associated with a poor prognosis, early disease relapse and predict treatment response and resistance (Foekens et al 2000;Borstnar et al 2002;Witte et al 1999b;Gouri et al 2016). High tissue levels of PAI-1 and uPA also led to a shorter DFS and OS in gastric, lung and ovarian cancer (Brungs et al 2017;Su et al 2015;Kuhn et al 1999).…”
Section: Discussionmentioning
confidence: 99%